Multi-Level Analysis of Inter-Provincial Differences in Fertility in Iran: The Case of Six Provinces with High and Low Fertility Rates - Serajeddin Mahmoudiani (Shiraz University of Medical Sciences, 2020)
Background: Identifying the effect of the social environment in which couples live and the demographic decisions are made, along with individual characteristics, are important in explaining human fertility. In the present study, an attempt was made to explain women's fertility in the six provinces using the multi-level analysis. Methods: The present study is a quantitative research with emphasis on the secondary analysis of the existing data.The statistical population consists of married women aged 15-49 living in the selected provinces. The sample included 95421 individuals. The selected provinces were Gilan, Mazandaran, Tehran, Sistan & Baluchistan, South Khorasan and Hormozgan. The census micro-data of population and housing in 2016 as well as some socio-economic indexes of selected provinces were analyzed using HLM software. Place of residence, educational level and employment status were individual variables, while income per capita as well as unemployment and literacy rates were the contextual variables. Also, the number of children ever born was considered as the fertility index or dependent variable. Results: The impact of individual variables on women's fertility is stronger than community effects. There were statistically significant inter-provincial differences in women's fertility. All the women's individual characteristics had a statistically significant impact on their fertility. Unemployment and literacy rates, as contextual effects, had a statistically significant impact on inter-provincial fertility. Conclusion: The inter-provincial differences in the fertility originate from their socio-economic circumstances. If the provinces' socio-economic circumstances become similar, the   convergence in fertility behavior across provinces may increase.